Properties of ethylene propylene diene monomer blended with recycled acrylonitrile butadiene rubber filled bamboo particulate (EPDM/rNBR) - Norhafizah Zaharudddin (School of Materials Engineering, 2016)
Characterization and properties of recycled acrylonitrile butadiene rubber (rNBR) and bamboo filers were analyzed by using FTIR and SEM on the surfaces. The ethylene propylene-diene monomer rubber (EPDM) blended with different size recycled NBR (rNBR) were studied at different formulation and blend ratio (95/5, 85/15, 75/25, 65/35 phr). The optimum blend ratio of EPDM/rNBR blends was then further studied by adding bamboo fillers as reinforcement.